Turkey Economic Monitor, April 2021 : Navigating the Waves - World Bank (World Bank, Washington, DC, 2021)
COVID-19 (coronavirus) has taken a heavy toll on Turkey, as it has across much of the world. New estimatesof total COVID-19 cases indicate that the epidemic grew rapidly over November and into December, before a new round of restrictions were put in place to control the spread of the virus in late December. The expansion of COVID-19 in late 2020 followed a similar path to many European countries. Turkey’s economic growth performance in 2020 was strong compared to other countries, but poverty spread, and unemployment became more prevalent. Turkey’s GDP grew by 1.8 percent in 2020, which was the fastest amongst G20 countries in 2020 aside from China. This was on the back of one of the strongest economic rebounds in the second half of 2020, largely achieved in the third quarter, but with positive growth continuing into the fourth quarter. Despite measures to support jobs and households, labor market and poverty outcomesnevertheless deteriorated. Indicators of domestic demand showed some signs of economic growth cooling early in 2021, although supply side measures such as industrial output remainedrobust. Turkey responded to COVID-19 with a large economic stimulus program, focused on credit channels. In fiscal terms, Turkey’s COVID-19 stimulus package amounted to nearly 12 percent of GDP when including tax deferrals and contingent liabilities. This is larger than the average for emerging market, G20 countries, and is similar in size to the stimulus packages of the United States, Australia and Canada. While the program utilized a broad range of fiscal tools, uniquely amongst G20 countries, Turkey’s support was overwhelmingly provided through the banking sector, and was not realized as direct fiscal costs on the budget, but ascontingent liabilities to the government in future. Credit stimulus, loose monetary policy, andother regulatory measures to promote credit expansion drove a sharp increase in economicactivity in late 2020. In addition to government measures to recapitalize a partial credit guarantee fund and state banks, policy interest rates were maintained below inflation and a series of financial regulatory measures introduced that incentivized banks to increase lending activities. The combined effect of these policies was to generate one of the largest credit expansions that the world saw in 2020.